2017
DOI: 10.1177/1179573517693802
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transporters in Central Nervous System Drug Delivery and Blood-Brain Barrier Protection: Relevance to Treatment of Stroke

Abstract: Ischemic stroke is a leading cause of morbidity and mortality in the United States. The only approved pharmacologic treatment for ischemic stroke is thrombolysis via recombinant tissue plasminogen activator (r-tPA). A short therapeutic window and serious adverse events (ie, hemorrhage, excitotoxicity) greatly limit r-tPA therapy, which indicates an essential need to develop novel stroke treatment paradigms. Transporters expressed at the blood-brain barrier (BBB) provide a significant opportunity to advance str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 122 publications
1
55
0
Order By: Relevance
“…Previous studies have confirmed OATP1A2 localization to brain microvascular endothelial cells (Bronger et al, 2005;Lee et al, 2005). Oatp1a4, the rodent ortholog of OATP1A2, is also expressed in microvascular endothelial cells in rat brain (Ronaldson et al, 2011;Thompson et al, 2014;Abdullahi et al, 2017a;Brzica et al, 2017Brzica et al, , 2018b. Previous studies in rodents have shown that Oatp1a4 can transport prototypical OATP substrates [taurocholate and 3-hydroxy-3methylglutaryl-CoA reductase inhibitors (i.e., statins)] (Ose et al, 2010;Ronaldson et al, 2011;Thompson et al, 2014;Abdullahi et al, 2017a;Brzica et al, 2018b).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies have confirmed OATP1A2 localization to brain microvascular endothelial cells (Bronger et al, 2005;Lee et al, 2005). Oatp1a4, the rodent ortholog of OATP1A2, is also expressed in microvascular endothelial cells in rat brain (Ronaldson et al, 2011;Thompson et al, 2014;Abdullahi et al, 2017a;Brzica et al, 2017Brzica et al, , 2018b. Previous studies in rodents have shown that Oatp1a4 can transport prototypical OATP substrates [taurocholate and 3-hydroxy-3methylglutaryl-CoA reductase inhibitors (i.e., statins)] (Ose et al, 2010;Ronaldson et al, 2011;Thompson et al, 2014;Abdullahi et al, 2017a;Brzica et al, 2018b).…”
Section: Introductionmentioning
confidence: 83%
“…The BBB is a formidable obstacle to CNS drug delivery that often renders treatment of brain diseases ineffective (Qosa et al, 2016). One such example is ischemic stroke, which is characterized by reduced oxygen and glucose supply to ischemic brain tissue (Liu et al, 2010;Brzica et al, 2017). Treatment of the ischemic core is impossible due to rapid development of necrosis (i.e., within minutes).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the extent to which adsorptive transcytosis mediate passage substances across the BBB is unclear, and still under investigation. Undisputedly, the majority of uptake to brain parenchyma surpassing BBB is mediated by carrier-mediated and receptor-mediated transport, where the molecule possesses high affinity to specific carrier or receptor expressed at the brain capillaries endothelial cells [11,12].…”
Section: The Challenges Of Bbb In Brain Drug Deliverymentioning
confidence: 99%
“…Astrocytes are thought to induce BBB properties such as the paracellular barrier or ABC transporter activities, whereas pericytes suppress peripheral endothelial cell properties in BCECs such as the significantly higher peripheral pinocytosis rate [10]. In the case of cerebral ischemia, the BBB is damaged within a few hours, whereby the TJ lose their integrity and some ABC transporters are regulated to protect the cells [5,17,28,41]. This loss of function can be measured by increased entry of permeability markers into the CNS.…”
Section: Introductionmentioning
confidence: 99%